Acacetin protects against depression-associated dry eye disease by regulating ubiquitination of NLRP3 through gp78 signal - Mingxia Xie; Mingxia Xie; Hanqing Wang; Jun Peng; Dongqin Qing; Xi Zhang; Dongwei Guo; Pan Meng; Pan Meng; Zhihong Luo; Xiaoye Wang; Qinghua Peng; et al. (Frontiers Media S.A., 2022)
Dry eye disease (DED) is a multifactorial syndrome that commonly occurs with depression. However, therapies targeting depression-related dry eye disease are rare. In the current study, we studied the beneficial effect of a natural flavone, acacetin, in depression-associated dry eye disease by utilizing the chronic unpredictable mild stress (CUMS) depression model. Our data showed that acacetin improved the depressive behaviors in sucrose preference test (SPT), tail suspension test (TST) and forced swim test (FST); relieved the dry eye symptoms including corneal epithelial impairments, tear production decrease and goblet cell loss in CUMS mice. Acacetin also inhibited NOD-like receptor protein 3 (NLRP3) inflammasome expression levels and suppressed inflammatory responses via enhancing glycoprotein 78 (gp78)/Insulin induced gene-1 (Insig-1)-controlled NLRP3 ubiquitination in CUMS mice. Furthermore, knockdown of gp78 compromised acacetin-conferred protective efficacy in depression-related dry eye disease. In summary, our findings indicated that acacetin exerts beneficial effect in depression-associated dry eye disease, which is tightly related to gp78-mediated NLRP3 ubiquitination.